The interdyscyplinary character of talent management - Sipa, Monika (Management and Administration Journal, 2020)
When looking at changes in the market, one can notice a growing interest in research on talent management. A talent shortage crisis is noticeable in many sectors and regions of world economies, thus it is necessary to focus more on that particular problem. However, talent management is a very complex issue. The main objective of the study was to determine the degree of scientists' interest in "talent management" and to identify the areas where the issue is discussed. To achieve the set objective, the Author using bibliometrics, analysed current research trends in leading scientific publications on talent management. The focus was on publications indexed in the SCOPUS and Web of Science databases.